Practical guide to cost estimating. (American Association of State Highway and Transportation Officials, 2013)
A State Department of Transportation's (DOT) ability to successfully manage and deliver its program is largely dependent on an ability to develop realistic estimates of project cost. Cost estimating involves not only the collection of relevant factors relating to the scope of a project and the cost of resources, but it also requires anticipating cost impacts that may occur due to changes in project scope, available resources, and national and global market conditions. This publication provides 'practical' guidance that serves those charged with the development of DOT cost estimates and with the management of the estimating process. This guidebook has two parts. Part I focuses on key cost-estimate techniques and Part II focuses on cost management activities.
"Publication Code: EST-1."
Keywords: Roads -- Design and construction -- Costs -- Estimates -- United States.; Highway engineering -- United States.; elektronické knihy; electronic books